Answer:
f(y) = 5(2.2y + 1) - 3 and h(y) = 11y + 2 are equivalent.
Explanation:
The functions are f(y) = 5(2.2y + 1) - 3, g(y) = 11y + 5 - y and h(y) = 11y + 2
Now, for y = 1,
f(1) = 5(2.2 + 1) - 3 = 16 - 3 = 13
g(1) = 11 + 5 - 1 = 15
h(1) = 11 + 2 = 13
Therefore, f(1) = h(1)
Now, for y = 2,
f(2) = 5(4.4 + 1) - 3 = 24
g(2) = 22 + 5 - 2 = 25
h(2) = 22 + 2 = 24
Hence, f(2) = h(2)
Now, for y = 3,
f(3) = 5(6.6 + 1) - 3 = 35
g(3) = 33 + 5 - 3 = 35
h(3) = 33 + 2 = 35
Hence, f(3) = g(3) = h(3)
But in case of f(y) and h(y) the values are same for y = 1, 2, 3.
So, f(y) = 5(2.2y + 1) - 3 and h(y) = 11y + 2 are equivalent.